2020
DOI: 10.1186/s13063-020-04845-7
|View full text |Cite
|
Sign up to set email alerts
|

Measles-mumps-rubella vaccine at 6 months of age, immunology, and childhood morbidity in a high-income setting: study protocol for a randomized controlled trial

Abstract: Background Measles is a highly contagious and serious infection. Before the introduction of vaccination, measles caused yearly epidemics putting vulnerable children at risk of brain damage and death. Despite safe and cost-effective vaccines, measles remains a leading cause of death in children globally. Due to insufficient vaccine coverage and low levels of in utero transferred antibodies from vaccinated mothers, outbreaks of measles in Denmark and other high-income countries are observed at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that infants aged 0–8 months were too young for routine immunization. The immunity in newborns was temporary and began to wane at 6 months of life, which made infants the most susceptible to rubella [ 42 , 43 ]. Another study found that women of childbearing age had lower levels of rubella antibodies, increasing the risk of congenital rubella syndrome in newborns to some extent [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that infants aged 0–8 months were too young for routine immunization. The immunity in newborns was temporary and began to wane at 6 months of life, which made infants the most susceptible to rubella [ 42 , 43 ]. Another study found that women of childbearing age had lower levels of rubella antibodies, increasing the risk of congenital rubella syndrome in newborns to some extent [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review is written by members of the 6 months MMR study at The Danish National University Hospital, Rigshospitalet. 72 The study is funded by the hospital and the innovation fund Denmark. All authors attest that they meet the ICMJE criteria for authorship.…”
Section: Discussionmentioning
confidence: 99%
“…The trial protocol is available elsewhere. 32 33 In Denmark, the measles vaccine is routinely given in combination with mumps and rubella at ages 15 months and 4 years. 34 Recruited infants were randomly allocated 1:1 either to intramuscular vaccination with the live attenuated M-M-R VaxPro vaccine containing measles virus (Edmonston strain, standard titre), mumps virus (Jeryl Lynn strain), and rubella virus (Wistar RA 27/3 strain) 35 or to intramuscular vaccination with placebo (solvent only) at age 5-7 months.…”
Section: Methodsmentioning
confidence: 99%